105 Virtual PCI with iFR-Pullback in Complex Coronary Disease: The Potential for Reducing Stent Length. (6th June 2015) - Nijjer, Sukhjinder; Sen, Sayan; Petraco, Ricardo; Al-Lamee, Rasha; Broyd, Christopher; Mayet, Jamil; Francis, Darrel; Davies, Justin; Mikhail, Ghada; Malik, Iqbal
Abstract : Background: Tandem and diffuse coronary disease presents an ongoing challenge and may necessitate multiple stents for optimal angiographic result at the cost of increased complications. Minimising stent length whilst achieving an acceptable physiological result may be clinically valuable but to date, physiological assessment is confounded by interaction in tandem disease. Pressure wire pullback using the instantaneous wave-free period (iFR) has less stenosis interaction, can predict the post-PCI result, permits virtual-PCI planning and, when motorised, can measure the physiological length of a stenosis. Applying this technology in a cohort of diffuse and tandem disease patients, we sought to assess what length of physiological stenosis requires treatment, to match a result considered acceptable in clinical practice. Methods: Intracoronary motorised pressure-wire pullbacks were performed under resting conditions in 32 coronary arteries with tandem and diffuse disease undergoing coronary intervention. Automated algorithms plotted ΔiFR/mm (iFR-intensity) for the length of the vessel and this was overlaid onto the coronary angiogram to create an iFR-pullback map. Coronary intervention was performed at the operator's discretion and a post-PCI iFR was measured. Virtual PCI using computer algorithms was performed on the iFR-pullback map, focusing upon areas of high iFR-intensity. The measurement of interest was the length of virtual stenting required to achieve the same virtual physiological result as observed in the real-world. Results: Pre-PCI iFR was 0.79 ± 0.03. The physiological length of the coronary lesions selected for intervention was significantly shorter than their anatomical length measured by quantitative angiography (12.6 ± 1.5 mm vs 23.3 ± 1.3 mm respectively, p < 0.001). PCI was performed using traditional angiographic guidance to achieve an iFR of 0.93 ± 0.01. The mean stent length used was 27.5 ± 2.3 mm which was significantly longer than physiological length (p < 0.001). Computer aided virtual PCI demonstrated the same physiological result could be achieved by treating only the areas of high pressure drop intensity, with a significantly larger gain in iFR per milimetre of stent deployed (1.1 ± 0.3%/mm versus 2.5 ± 0.72%/mm, p = 0.005). Conclusion: Physiological lesion length is shorter than anatomical lesion length. Stenting only areas of high physiological intensity may theoretically achieve an optimal physiological result with shorter overall stent lengths. Further studies are required to confirm the clinical safety of focal stenting and the long-term utility of physiological optimisation as opposed to angiographic optimisation. Co-registration of physiological data such as ΔiFR/mm with angiographic and intracoronary imaging may provide a tool to optimally plan intervention for complex coronary lesions.